(untitled) (Indonesian Sports Justice Review, 2024)
Gender inequality remains a significant issue in Indonesian sports, particularly in leadership positions, where women continue to face systemic barriers to entry and advancement. This paper explores the gender gaps in sports leadership, analyzing the factors that contribute to the underrepresentation of women in decision-making roles within sports organizations, federations, and government bodies. The study highlights how gender biases, cultural norms, and limited opportunities for professional development hinder women’s participation in sports governance. Through qualitative interviews with female athletes, coaches, and sports administrators, the paper identifies both institutional and societal barriers to gender equality in sports leadership. It concludes by proposing strategies for fostering a more inclusive sports system, including mentorship programs, gender quotas, and policy reforms aimed at promoting women’s leadership in Indonesian sports.